DEVELOPMENT OF FACILITIES AND SERVICES OF THE WAY KALAM WATERFALL NATURAL TOURISM DESTINATION, SOUTH LAMPUNG BASED ON VISITOR PERCEPTIONS - Nadia Ghassani; Gunardi Djoko Winarno; Bainah Sari Dewi; Sugeng P. Harianto (University of Lampung, 2023)
The Way Kalam Waterfall tourist attraction is one of the natural attractions that has tourist attraction and potential and can be developed with development and strategy because it can be used to develop facilities and services. Based on the explanation above, the aim of this research is to analyze the condition of facilities and services at the Way Kalam Waterfall destination based on visitor assessments for the development of Nature Tourism. This research was carried out at the Way Kalam Waterfall Natural Tourism Object located in Way Kalam, South Lampung Regency, Lampung. Research data collection was carried out in September 2023. The method used was a questionnaire and also direct observation with 100 visitors as respondents based on the Slovin formula with random sampling techniques, then analyzed using descriptive analysis and a Likert scale. Based on the results of the analysis of visitors' perceptions of the Way Kalam Waterfall natural tourism destination, efforts are needed to develop facilities and services for the Way Kalam Waterfall natural tourist attraction. This is because the facilities and services are inadequate, such as the absence of an information center, the condition of the toilets which are still one with changing and rinsing rooms, the prayer rooms are not suitable, and there are no counters. The condition of the Way Kalam Waterfall natural tourism destination is good, but there are several things that need to be improved, especially infrastructure and additional facilities and services. The assessment of the condition of the Way Kalam Waterfall Nature Tourism destination based on visitors is in a good category, but the facilities and services have an average facility value of 2, which means inadequate.